Is There an Association Between Metabolic Syndrome and Cognitive Function in Very Old Adults? The Newcastle 85+ Study. Issue 4 (8th April 2015) - Harrison, Stephanie L.; Stephan, Blossom C. M.; Siervo, Mario; Granic, Antoneta; Davies, Karen; Wesnes, Keith A.; Kirkwood, Thomas B. L.; Robinson, Louise; Jagger, Carol
Abstract : Objectives: To determine, using data from the Newcastle 85+ Study, whether there is an association between modern diagnostic criteria for metabolic syndrome (MetS) and cognitive function in very old adults (≥85) and whether inflammation, physical activity, or diabetes mellitus status affects this association. Design: Longitudinal, population‐based cohort study. Setting: Newcastle and North Tyneside, United Kingdom. Participants: Community‐dwelling and institutionalized men and women recruited through general practices (N = 845). Measurements: MetS was defined according to the National Cholesterol Education Program (NCEP) Adult Treatment Panel III (ATP III) criteria. Cross‐sectional and prospective (up to 5 years of follow‐up) associations between MetS and global cognitive function (assessed using the Mini‐Mental State Examination (MMSE)) and between MetS and attention and episodic memory (assessed using the Cognitive Drug Research battery) were performed. Results: MetS was not associated with cognitive function at baseline or cognitive change over time. Lack of association was not because MetS was predictive of subsequent mortality. Of the individual components of the MetS criteria, high blood pressure was associated with better cognitive function at baseline (MMSE: β (standard error (SE)) = −0.716 (0.152), P  < .001), and low high‐density lipoprotein cholesterol was associated with poorer global cognitive function at baseline (MMSE: 0.436 (0.131), P  = .001). Conclusion: The association between MetS and cognitive decline, which has been described in younger populations (<75), was not apparent in this population of individuals aged 85 and older at baseline.